Application of the Videosensory Method in Teaching Gymnastic Exercises to Students - Tursunpulatovich, Mukhammadiyev Navruz (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses the methods of teaching gymnastics to students of higher educational institutions of a sports profile. Advice and instructions are given for the use of the video-sensory method in teaching students gymnastic exercises.